Seeds of Success: How Government Grants aid early-stage Startup Performance? : A quantitative research on government grants in the Nordic Context - Hirsimäki, Juuso (My University, 2024)
The startup ecosystems of the Nordic countries have been growing significantly during the last decade. As the global business environment is changing, the focus countries of the study, Finland, Sweden, and Norway, have all noticed a need to focus on knowledge-intensive industries thriving with innovation and research. Startups are focal engines in the midst of these industries, which are agile and ambitious companies constantly fighting serious adversities to become leaders in their respective fields. To alleviate these adversities, the Nordic countries have established government-run grant programs that offer either funding or mentoring services to their domestic startups. No previous research on Nordic government grants had been done, and due to the remarkable significance of the growing startup ecosystems for the countries, the role of these grants as supportive instruments is relatively high. Moreover, the academic literature, in general, provides very little information on the effectiveness of government grants, and especially on what features make a government grant effective in supporting startups to survive and later prosper. These findings validated the need for this research. The objectives of this research were divided into two separate entities. Firstly, the study aimed to investigate how effective government grants are in supporting early-stage startups and consequently creating societal value in the Nordic countries. Secondly, it explored why some government grants perform better than others. The study was conducted as a quantitative analysis supported by an extensive literature review. Five grants and 678 companies were included from Finland, Sweden, and Norway. Multiple statistical analysis methods were utilized, including linear and binary logistic regression analyses. The study found that the Nordic startup grants had a significant positive impact on their domestic startups. The effect was noticed as significant on all three performance indicators used: employee growth, survival rate, and funding rate. Furthermore, the study found no government grant features to significantly influence above-average performance. However, weak signals were found, implying that mentoring services and thorough application processes positively impact startup performance. Moreover, grant size was not found to significantly impact government grant performance. As the significance of the Nordic startup ecosystems has increased rapidly, further research is needed, where a more significant heterogeneity of studied grants is advised.

Pohjoismaisen startup-ekosysteemit ovat kasvaneet merkittävästi viimeisen vuosikymmenen aikana. Maailman liiketoimintaympäristön muuttuessa tutkimuksen kohteena olleet maat, Suomi, Ruotsi ja Norja, ovat kaikki huomanneet tarpeen keskittyä innovoimiseen sekä tietointensiivisiin teollisuudenaloihin. Startupit ovat keskeisiä moottoreita näiden alojen kehitykselle. Ne ovat ketteriä ja kunnianhimoisia yrityksiä, jotka taistelevat jatkuvasti ankarien haasteiden kanssa tullakseen johtaviksi yrityksiksi omilla aloillaan. Näiden haasteiden lievittämiseksi Pohjoismaat ovat perustaneet hallitusten hallinnoimia apurahaohjelmia, jotka tarjoavat joko rahoitusta tai mentorointipalveluita kotimaisille startupeilleen. Aiempaa tutkimusta liittyen Pohjoismaisten hallitusten myöntämiin apurahoihin ei oltu tehty, ja kasvavien startup-ekosysteemien suuren merkityksen vuoksi näiden avustusten rooli tukivälineinä on verrattaen korkea. Lisäksi yleinen akateeminen kirjallisuus tarjoaa hyvin vähän tietoa hallituksen myöntämien avustusten tehokkuudesta, ja erityisesti siitä, mikä tekee apurahasta tehokkaan startupien selviytymisen ja myöhemmän menestymisen tukemisessa. Nämä löydökset toimivat tämän tutkimuksen motiiveina. Tutkimuksen tavoitteet jaettiin kahteen erilliseen kokonaisuuteen. Ensiksi tutkimuksen tavoitteena oli tutkia, kuinka tehokkaita hallituksen myöntämät apurahat ovat varhaisvaiheen startupien tukemisessa ja siten yhteiskunnallisen arvon luomisessa Pohjoismaissa. Toiseksi pyrittiin vastaamaan siihen, miksi jotkut hallituksen myöntämät apurahat suoriutuvat paremmin kuin toiset. Tutkimus toteutettiin kvantitatiivisena analyysina, jota tuki laaja kirjallisuuskatsaus. Tutkimukseen sisältyi viisi apurahaa ja 678 yritystä Suomesta, Ruotsista ja Norjasta. Tutkimuksessa hyödynnettiin useita tilastollisia analyysimenetelmiä, kuten lineaarista regressioanalyysiä ja binääristä logistista regressioanalyysiä. Tutkimus osoitti, että Pohjoismaiden startup-apurahoilla oli merkittävä positiivinen vaikutus maiden kotimaisiin startupeihin. Vaikutus oli havaittavissa kaikissa kolmessa käytetyssä suorituskykymittarissa: työntekijämäärän kasvu, selviytymisaste ja rahoitusaste. Tutkimus ei havainnut apurahojen ominaisuuksia, jotka hyvin merkittävästi vaikuttaisivat niiden suorituskykyyn. Tutkimuksessa löydettiin kuitenkin heikkoja signaaleja, jotka viittaavat siihen, että mentorointipalvelut ja perusteelliset hakuprosessit vaikuttavat myönteisesti tuettujen startupien suorituskykyyn. Lisäksi huomattiin, että apurahojen koko ei vaikuttanut merkittävästi niiden suorituskykyyn. Pohjoismaisten startup-ekosysteemien voimakkaan kasvun myötä lisätutkimukselle on perusteltu tarve, missä suositellaan käytettävän heterogeenisempaa joukkoa tutkittavia apurahoja.
Keywords: government grant, startup, early-stage, Nordics, apuraha, startup, Pohjoismaat